Establishing the Swiss Spinal Tumor Registry (Swiss-STR): a prospective observation of surgical treatment patterns and long-term outcomes in patients with primary and metastatic spinal tumors - Nevzati, Edin; Poletti, Nicolas; Spiessberger, Alexander; Bäbler, Sabrina; Studer, Gabriela; Riklin, Christian; Diebold, Joachim; Chatain, Grégoire P.; Finn, Michael; Witt, Jens-Peter; Moser, Manuel; Mariani, Luigi (Frontiers in Surgery, 2023)
Background: Tumors of the vertebral column consist of primary spinal tumors and malignancies metastasizing to the spine. Although primary spine tumors are rare, metastases to the spine have gradually increased over past decades because of aging populations and improved survival for various cancer subtypes achieved by advances in cancer therapy. Metastases to the vertebral column occur in up to 70% of cancer patients, with 10% of patients demonstrating epidural spinal cord compression. Therefore, many cancer patients may face spinal surgical intervention during their chronic illness; such interventions range from simple cement augmentation over decompression of neural elements to extended instrumentation or spinal reconstruction. However, precise surgical treatment guidelines do not exist, likely due to the lack of robust, long-term clinical outcomes data and the overall heterogeneous nature of spinal tumors. Objectives of launching the Swiss Spinal Tumor Registry (Swiss-STR) are to collect and analyze high-quality, prospective, observational data on treatment patterns, clinical outcomes, and health-related quality of life (HRQoL) in adult patients undergoing spinal tumor surgery. This narrative review discusses our rationale and process of establishing this spinal cancer registry. Methods: A REDCap-based registry was created for the standardized collection of clinical, radiographic, surgical, histological, radio-oncologial and oncological variables, as well as patientreported outcome measures (PROMs).Discussion: We propose that the Swiss-STR will inform on the effectiveness of current practices in spinal oncology and their impact on patient outcomes. Furthermore, the registry will enable better categorization of the various clinical presentations of spinal tumors, thereby facilitating treatment recommendations, defining the socio-economic burden on the healthcare system, and improving the quality of care. In cases of rare tumors, the multi-center data pooling will fill significant data gaps to yield better understanding of these entities. Finally, our two-step approach first implements a highquality registry with efficient electronic data capture strategies across hospital sites in Switzerland, and second follows with potential to expand internationally, thus fostering future international scientific collaboration to further push the envelope in cancer research.